Case Report: IgA Nephropathy in a Patient With Anti-Transcription Intermediary Factor-1γ Antibody-Positive Dermatomyositis - Zhang, Suo; Chen, Yu-Lan; Liu, Cui-Lian; Xie, Jing-Yi; Sun, Bao-Dong; Liu, Dong-Zhou (Frontiers in Immunology, 2022)
Immunoglobulin A nephropathy (IgAN) is the most common primary glomerulonephritis characterized by IgA deposits in the mesangial area of glomeruli. Connective tissue disorders are some of the most frequent causes of secondary IgAN. Nevertheless, IgAN rarely occurs in systemic autoimmune myopathies (SAMs). The present case study reports on a 58-year-old patient with dermatomyositis with positive anti-transcription intermediary factor (TIF)-1γ antibodies who was diagnosed with IgAN during standard immunosuppressive therapy. Moreover, we have made a systematic review regarding the association of SAMs and IgAN. To the best of the authors’ knowledge, this is the first case study describing a patient with anti-TIF1γ antibody-positive dermatomyositis who developed IgAN, which demonstrates a potential relationship between anti-TIF1γ-positive dermatomyositis and IgAN. It is important for clinicians to be aware of the possibility of renal involvement in patients with SAMs, even in those with anti-TIF1γ-positive dermatomyositis.